Gloeothece sp.—exploiting a new source of antioxidant, anti-inflammatory, and antitumor agents - Amaro, HM (2021)
Bioactive lipidic compounds of microalgae, such as polyunsaturated fatty acids (PUFA) and carotenoids, can avoid or treat oxidation-associated conditions and diseases like inflammation or cancer. This study aimed to assess the bioactive potential of lipidic extracts obtained from Gloeothece sp.–using Generally Recognized as Safe (GRAS) solvents like ethanol, acetone, hexane:isopropanol (3:2) (HI) and ethyl lactate. The bioactive potential of extracts was assessed in terms of antioxidant (ABTS•+, DPPH•,• NO and O2• assays), anti-inflammatory (HRBC membrane stabilization and Cox-2 screening assay), and antitumor capacity (death by TUNEL, and anti-proliferative by BrdU incorporation assay in AGS cancer cells); while its composition was characterized in terms of carotenoids and fatty acids, by HPLC-DAD and GC-FID methods, respectively. Results revealed a chemopreventive potential of the HI extract owing to its ability to: (I) scavenge- NO• radical (IC50, 1258 ± 0.353 µg·mL-1 ); (II) inhibit 50% of COX-2 expression at 130.2 ± 7.4 µg·mL-1; (III) protect 61.6 ± 9.2% of lysosomes from heat damage, and (IV) induce AGS cell death by 4.2-fold and avoid its proliferation up to 40% in a concentration of 23.2 ± 1.9 µg·mL-1 . Hence, Gloeothece sp. extracts, namely HI, were revealed to have the potential to be used for nutraceutical purposes.